2021
DOI: 10.1103/physrevx.11.041035
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Screening for Terahertz Detection with Machine-Learning-Based Methods

Abstract: The molecular requirements are explored for achieving efficient signal up-conversion in a recently developed technique for terahertz (THz) detection based on molecular optomechanics. We discuss which molecular and spectroscopic properties are most important for predicting efficient THz detection and outline a computational approach based on quantum-chemistry and machine-learning methods for calculating these properties. We validate this approach by bulk and surface-enhanced Raman scattering and infrared absorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…The creation of the database is described in Ref. [2]. DFT calculations are performed at the B3LYP+D3/def2-SVP level using the Gaussian program package.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The creation of the database is described in Ref. [2]. DFT calculations are performed at the B3LYP+D3/def2-SVP level using the Gaussian program package.…”
Section: Methodsmentioning
confidence: 99%
“…where M refers to the set of normal modes that have frequencies in the range defined by the user. These properties are standardized as described in Ref [2]. A, R, and P can also be calculated using orientation-specific intensities, this enables fast comparison of molecular performance at different orientations.…”
Section: Definitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…To understand the frequency-selective dependence, we calculate the product [in m 3 /(mol·sr)] of infrared absorption and Raman intensity of BPT, averaged over all orientations for each normal mode (Fig. 4A and supplementary materials, section S1) ( 24 ). This clearly showed that the optimum overlap of optical and vibrational modes was at 1080 cm −1 , and that the dipoles were all well aligned with the vertical E field in the nanogap at both visible and MIR wavelengths.…”
mentioning
confidence: 99%
“…S3). Prospects for multiband operation are promising [selection of optimal molecules is required to broaden the vibrational range and responsivity ( 24 )] because lower-frequency anti-Stokes emission has already been observed at 250 cm −1 (Fig. 3Β, λ = 40 μm or 7.5 THz).…”
mentioning
confidence: 99%